THE IMPACT OF MULTIFACETED VACCINATION INTERVENTIONS ON MEASLES ERADICATION: A BEHAVIORAL ANALYSIS OF THE SEITRV EPIDEMIC MODEL - Kolawole, Mutairu Kayode; Akin-Awoniran, Bukola Olayemi (FUDMA JOURNAL OF SCIENCES, 2025)
Despite the effectiveness of the vaccine, measles is still a major worldwide health concern. Human behavior, including vaccine reluctance and reactions to health initiatives, is examined in this study. This study uses a thorough SEITRV (Susceptible–Exposed–Infectious–Treated–Recovered–Vaccinated) model to examine how different vaccination campaigns impact measles transmission via the lens of human behavior. Using both epidemiological and behavioral characteristics, an SEITRV model was created to mimic the spread of measles. We modeled treatments including treatment availability, education campaigns, and mass and targeted immunization. Simulations assessed how public behavior affects the spread of disease using data from previous outbreaks. According to simulation studies, vaccination intervention has a major impact on how measles outbreaks develop. Models that took vaccination awareness into account. Strategies that combined strong public education with high vaccination rates, in particular, showed the biggest drops in disease prevalence. These results highlight how ineffective vaccination coverage is on its own in controlling disease This study emphasizes that mass vaccination for controlling measles and behavioral variables like vaccination reluctance and public response to health campaigns must also be addressed by public health methods. The efficacy of disease control initiatives is increased when medical interventions are combined with focused initiatives to change public perceptions and behavior. Therefore, effective measles containment and eventual eradication require a dual focus on clinical and behavioral interventions.
Keywords: Measles; Vaccine; SEITRV model; Vaccination; Educational programme; Eradication